Multiparametric analysis of host and parasite elements in new world tegumentary leishmaniasis - de Carvalho, Bruna Caroline; Vital, Tamires; Osiro, Jaqueline; Gomes, Ciro Martins; Noronha, Elza; Dallago, Bruno; Rosa, Ana de Cássia; Carvalho, Juliana Lott; Hagström, Luciana; Hecht, Mariana; Nitz, Nadjar (Frontiers in Cellular and Infection Microbiology, 2022)
Tegumentary leishmaniasis is a tropical disease caused by protozoa of the genus Leishmania. Clinically, the disease presents a broad spectrum of symptoms, the mechanisms underlying the development of lesions remaining to be fully elucidated. In the present work, we performed a correlation and multiparametric analysis to evaluate how parasite- and host-related aspects associate with each other, and with the different clinical manifestations of tegumentary leishmaniasis. This cross-sectional study involved 75 individuals from endemic areas of Brazil, grouped according to their symptoms. Leishmania species were determined by DNA sequencing, and parasite load, antibody production, and cytokine profile were evaluated by kDNA qPCR, ELISA, and flow cytometry. Data were analyzed using the Chi-square test, principal component analysis, canonical discriminant analysis, and correlation analysis. Among the recruited patients, 23 (31%) were asymptomatic, 34 (45%) had primary cutaneous leishmaniasis, 10 (13%) presented recurrent cutaneous leishmaniasis, and eight (11%) had mucocutaneous leishmaniasis. Leishmania species identified included L. amazonensis, L. braziliensis, and L. guyanensis. Surprisingly, no Leishmania RNA virus infection was detected in any sample. In summary, our work showed that parasite load, antibody production, and cytokine levels alone are not determinants for tegumentary leishmaniasis symptoms. However, the correlation analysis allowed us to observe how these factors are correlated to each other within the groups, which revealed a unique network for each clinical manifestation. Our work reinforces the complexity of tegumentary leishmaniasis outcomes - which are associated with multiple host and parasite-related elements and provides a holistic model of the disease.